Sustainable development in practice sustainomics methodology and applications - Munasinghe, Mohan (Cambridge University Press, 2009)
This book provides a practical analysis of current sustainable development prospects by applying the innovative sustainomics framework. It explains the key principles underlying sustainomics, illustrates the methodology with wide-ranging empirical and policy-relevant case studies, and is useful for students, researchers, policy analysts and development practitioners.